Improving the flexibility and durability of aged paper with bacterial cellulose. (August 2022) - Wu, Xiao; Mou, Hongyan; Fan, Huiming; Yin, Jiayuan; Liu, Yibei; Liu, Jianan
Abstract: Ancient paper with irreplaceable value was severely acidified and aged due to poor storage conditions and the degradation of its own components. The restoration of ancient paper in deacidification and reinforcement was imperative. Bacterial cellulose (BC) with good fiber aspect ratio and rich hydroxyl groups was suitable to enhance aged paper. However, the utilization of BC for paper reinforcement was limited with its dispersion due to the highly aggregated state. In this paper, stable BC solutions were prepared by dissolving BC in NaOH/urea, and its application in ancient paper restoration by ultrasonic atomization was proposed. BC was uniformly bridged on the fiber surface and between the fibers, which played a good role in strengthening the aged paper. After treatment, the mechanical strength of the paper was notably improved, the paper processed for 60 min using 0.6% BC solution exhibited a high folding resistance of 28 times, which was 2.15 times of the untreated paper. Besides, the pH value and alkali reserves of the repaired paper were successfully achieved at 8.12 and 0.4 mol/kg. Even after hot-humid aging for 30 d, the repaired paper retained about 50% of its initial strength. This suggested the repair fluid based on BC had potential applications in the field of paper reinforcement with high performance and durability. Graphical Abstract: ga1 Highlights: BC was employed to reinforce aged paper by ultrasonic atomization. The combination of nanostructured BC and aged paper fibers was promoted by the surface tension and binding force of papers due to the water evaporation. The mechanical strength and alkali reserves of the repaired paper were significantly improved. The BC-repaired paper had good stability to resist the hot-humid aging.